Everyday math demystified - Gibilisco, Stan (New York : McGraw-Hill, 2013)
'More than 2 million books sold in the DeMYSTiFieD series! A straightforward, step-by-step approach for fast and fun mastery of everyday math from the trusted DeMYSTiFieD brand'--
Includes bibliographical references and index.
Keywords: Mathematics -- Popular works; Mathematics -- Programmed Instruction